Aggressive forms of pituitary adenomas (literature review and clinical observation) - P. L. Kalinin; Yu. Yu. Trunin; D. V. Fomichev; I. V. Chernov; M. V. Ryzhova (Опухоли головы и шеи)
Introduction. Pituitary adenomas comprise 10–15 % of all intracranial tumors. Despite being benign tumors, 25–55 % of them exhibit invasive growth spreading into surrounding structures (sphenoid sinus, cavernous sinus, etc.). In literature, there isn’t a generally accepted definition of aggressive pituitary adenomas. As a result, there aren’t any studies reporting on the therapy of choice for this disease, except for several reports on using temozolomide as a “salvage” therapy in patients who didn’t respond to standard treatment methods.We present a clinical observation of a patient with “refractory” pituitary adenoma who successfully underwent 4 surgical interventions and 2 courses of high-dose stereotactic radiotherapy.Results. Application of stereotactic radiotherapy at high (59.4 Gy) dose, which is usually used for treatment of patients with malignant tumors, allowed to achieve long recurrence-free period of 5.5 years (65 months). Observation has shown that repeated courses of stereotactic irradiation can be sufficiently effective and safe in patients with large and gigantic tumors including “refractory” pituitary adenoma.Conclusion. Further studies are necessary for specification of parameters of “refractory” adenomas and their detection at the early stages of diagnosis. Confirmed diagnosis requires more aggressive surgical, radiological, and drug treatment.